Proecological ways of shaping green areas - proposals for the Ursynów district of Warsaw - Staroszczyk, Justyna; Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2008)
It is well known that green areas are a significant component of urban environment. Plants influence urban conditions in many ways; they have a positive effect on both people’s health and environmental issues, there are many reasons why the proportion of green areas in cities should be increased. It is important to take advantage of plant properties and suitable methods of shaping green areas to benefit nature. The article emphasizes the importance of comprehensive environmental protection. It presents selected methods of shaping green areas and nursing plants, which are in common use in Western Europe and USA, but are under-used in Poland, the main aim of the article is to propose solutions which allow to shape green areas in the Ursynów district of Warsaw in favor of environmental protection e.g. in a way that makes it possible to preserve biodiversity or reduce drink water use.